Archaeological Evidence of Jewish Settlement in a 'Forbidden Town of Tyre' in the Aftermath of the Bar-Kokhva Revolt - Fridman, Reʾuven ca. 20./21. Jh. (Zeitschrift des Deutschen Palästina-Vereins, 2020)
2nd - 3rd cent. C.E. rabbinic texts reflect a Jewish presence in an enclave of ancient Phoenicia known in the rabbinic texts and the scholarly literature as the 'Forbidden Towns in the Territory of Tyre'. This paper presents archaeological evidence of a Jewish presence contemporary with the rabbinic texts at the site of ancient Shezet, one of the 'forbidden towns' listed in the texts. The site was not identified by the Palestine Exploration Fund Survey of Western Palestine and does not appear on the Palestine Exploration Fund Maps. The historical and archaeological evidence indicates that the settlement was founded in the 2nd - 3rd cent. C.E., during or in the aftermath of the persecutions following the Bar-Kokhva revolt. The Jewish presence is confirmed by testing a pair of rock-carved, plastered, stepped-pools at the site using the most current methodologies for identifying Jewish ritual immersion pools (miqwā'ōt).